PENGARUH RELAKSASI BENSON TERHADAP TINGKAT STRES PADA LANSIA DI DESA SALENRANG KEC. BONTOA KAB. MAROS - Syahrir; Fatmawati (Jurnal Ilmiah Keperawatan dan Kebidanan Holistic Care, 2022)
Elderly is part of the process of growth and development, humans do not suddenly grow old, but develop from infants, children, adults and the elderly. One of the causes of health problems in the elderly is unpreparedness and efforts to fight the changes experienced in old age which puts individuals of this age in a wrong position which eventually becomes a source of accumulated stress. One effort to deal with stress is the relaxation method. This technique is called Benson relaxation, which is a procedure to help individuals deal with stressful situations and efforts to relieve stress. The research objective was to determine the effect of benson relaxation on reducing stress levels in the elderly. The method in this study used a quasiexperimental design with one group pretest-posttest involving 30 respondents from 285 populations. Measuring tool used in research is a questionnaire. The results of this study were analyzed by the Wilcoxon test, which showed that the elderly before being given the Benson relaxation experienced 5 mild stress (16.7%) and 25 moderate stress (83.3). Meanwhile, after being given Benson relaxation, 17 (56.7%) experienced mild stress and 13 (43.3%) moderate stress. The conclusion is that there is the effect of benson relaxation on reducing stress levels in Salenrang Village, Kec. Bontoa Kab. Maros. It is hoped that the elderly can apply this Benson relaxation technique to overcome the stress experienced in everyday life